PERENCANAAN PENGGUNAAN LAHAN UNTUK PENGEMBANGAN AGROFORESTRI DI DAS CILIWUNG HULU PROVINSI JAWA BARAT - Rini Fitri; Surya Darma Tarigan; Santun R.P. Sitorus; Latief M Rachman (Diponegoro University, 2018)
Land use has become one of the causes of watershed damage, resulting in complex physical, economic and social problems in both upstream and downstream. This study aims to determine the direction of land use planning for the development of agroforestry in the Upstream of Ciliwung River Watershed of West Java Province. The orientation of the land use planning for agroforestry development was conducted by determining the type of agroforestry to be developed, the land capability class, as well as soil and water conservation agroforestry techniques to be applied. The results of this study showed that the determination of the agroforestry land use planning in the Upstream of Ciliwung River Watershed of West Java Province is directed to the development of agroforestry. Plant recommended to be developed on agroforestry land use include the annual crops combined with seasonal crops, and the application of conservation techniques; including terrestrial, gulud terrace, mulching, and terrace strengthening-plant.